Preservation of Traditional Sports of Geudeu-Geudeu Wrestling With Modification of Match Rules in the Pidie Jaya Community of Aceh - Edi Safwan; Naimatul Jamaliah; Zulfikri (Journal Coaching Education Sports, 2022)
The growth of traditional sports begins with daily habits with various activities in the form of movements towards a game which contains elements of the art of sports and social values ​​that exist throughout Indonesia. The aim of the study was to modify the rules of the traditional sport of geudeu-geudeu wrestling. The research method used is research and development (R & D) with the stages of the ADDIE method, namely: analyze, design, develop, implement, evaluate. The research instruments were questionnaires and interviews containing statements related to the modification of the traditional sport rules of geudeu-geudeu wrestling. The research subjects were geudeu-geudeu trainers and 10 youths in Pidie Jaya Regency. Data analysis by looking for the magnitude of the relative frequency or in the form of a percentage. The results of this study indicate that there are four alternative answers chosen by respondents, namely 62.23% strongly agree, 34.24% choose agree, and 3.53% disagree, with the modification of the geudeu-geudeu martial arts regulations. Youth 60.02% strongly agree, 36.55% agree, 3.43% disagree with the modification of the traditional sport rules of geudeu-geudeu wrestling. Geudeu-geudeu and youth coaches 60.12% strongly agreed, 35.39% agreed with the development of the traditional sport regulations of geudeu-geudeu wrestling, and 4.49% disagreed with the modification of the traditional sport rules of geudeu-geudeu wrestling.